2015
DOI: 10.1016/j.aogh.2015.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Fall Injuries in Nepal: A Countrywide Population-based Survey

Abstract: The Nepal SOSAS study provides countrywide, population-based data on fall-injury prevalence in Nepal and has identified falls as a crucial public health concern. These data highlight persistent barriers to access to care for the injured and the need to improve trauma care systems in developing countries such as Nepal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 17 publications
(15 reference statements)
2
25
0
1
Order By: Relevance
“…6,11,13,25,27,28,33 The majority (n = 248, 51%) of falls occurred at the ground level, which is similar to that reported earlier. 11,27,28 Results of a multivariate logistic regression demonstrated that type of residence, number of members in the family, type of cooking area, and whether the mother was alive were significantly associated with fall injuries. Moreover, the surrounding environment plays a crucial role in the occurrence of injuries; rural outmigration has resulted in overcrowded cities, which makes children living in urban areas more prone to unintentional fall-related injuries.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…6,11,13,25,27,28,33 The majority (n = 248, 51%) of falls occurred at the ground level, which is similar to that reported earlier. 11,27,28 Results of a multivariate logistic regression demonstrated that type of residence, number of members in the family, type of cooking area, and whether the mother was alive were significantly associated with fall injuries. Moreover, the surrounding environment plays a crucial role in the occurrence of injuries; rural outmigration has resulted in overcrowded cities, which makes children living in urban areas more prone to unintentional fall-related injuries.…”
Section: Discussionsupporting
confidence: 87%
“…Our study reports a higher incidence of injuries in Ujjain than that reported by other studies from India 20,[24][25][26][27] and Nepal, which reported an incidence of 5.72% among children between 0 and 14 years of age. 28 Other LMICs also reported a high incidence of childhood fall injuries. [29][30][31][32] A total of 338 (69%) fall injuries received first aid and 40 (8%) falls resulted in hospital admissions.…”
Section: Discussionmentioning
confidence: 99%
“…The study estimated death and disability from every cause of injury for all ages and both sexes over a time range spanning from 1990 to 2017 2–7. Past research and commentaries have focused on changes in the injury burden in Nepal and have attributed trends in injury burden to rapid urbanisation, infrastructure development, increasing numbers of new and old vehicles (mainly two-wheeler motorised vehicles), poorly designed roads, limited prehospital and emergency care, poor healthcare infrastructure and rehabilitation services, an ageing population and natural disasters 8–17. Catastrophic events in Nepal, such as the 2015 massive earthquake and its aftershocks, which killed approximately 9000 and injured over 22 000 people, are known to contribute significantly to the burden of injury 14…”
Section: Introductionmentioning
confidence: 99%
“…A large populationbased survey was conducted in 2014 inventorising basic demographic properties and perceived unmet needs and disabilities of the populations of Nepal, Rwanda and Sierra Leone. Various cross-sections based on this data set were described and published before [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], mainly focusing on Nepal. The aim was to evaluate the unmet surgical needs and perceived disabilities of the people of Nepal.…”
Section: Introductionmentioning
confidence: 99%